Sejarah Perkembangan Sistem Pendidikan Islam di Pesantren Ar-Raudlatul Hasanah Kota Medan - Andre Syahbana Siregar (UIN Sumatera Utara Medan, 2018)
This research aims to discuss about Islamic education, especially the pesantren institution which located in Medan. Pesantren Ar-Raudhlatul Hasanah is an object in this research by using the qualitative method and field research. About 34 years, this pesantren became an important part to developing Islamic education and furthermore to build the character Indonesian generations, especially in Medan. This pesantren also have santri (student) whose came from neighbors state, such as Malaysia and Thailand. As a modern education institution, this pesantren success to integrate between the Kuliiyatul Mu’allimin Al-Islamiyah as the curriculum which adopted from Modern Pesantren Gontor and the National Curriculum. So this pesantren have three roles: as the pesantren, the madrasah, and the school.Keywords:Pesantren Ar-Raudlatul Hasanah, Islamic education system, character of the nation.